2023
DOI: 10.37256/aecm.4220232941
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of SnO2/WO3 Bilayers Prepared by Reactive DC Sputtering

Abstract: The combination of transparent and conductive SnO2 with colored WO3 thin films has interesting uses in electrochromic windows, photovoltaic cells and photocatalytic systems, where the SnO2/WO3 bilayer can improve the device efficiency by increasing the charge separation and extending the energy range of photoexcitation. In this work, SnO2 and WO3 thin films were prepared by reactive DC sputtering from Sn and W targets, respectively. Single layers and bilayers deposited on glass substrates have been analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Interestingly, the Raman spectra collected upon the agglomerates show features compatible with a higher crystalline character, which is slightly improved by annealing, as confirmed by the sharp signal around 810 cm −1 and by the appearance of the small shoulder around 710 cm −1 after annealing at 120 °C and 150 °C (curves (C) and (D) in the left panel) [56]. It is worth mentioning that the intensity of the shoulder at 710 cm −1 is still very small and that the Raman spectra all share a common feature around 950 cm −1 , which is characteristic of amorphous WO3 films [57]. All these observations, together with the XRD suggest that the slot-die-deposited WO3 films are characterized by a prevalent amorphous general character.…”
Section: Pure Wo 3 Films: Structural and Morphological Characterizationmentioning
confidence: 87%
“…Interestingly, the Raman spectra collected upon the agglomerates show features compatible with a higher crystalline character, which is slightly improved by annealing, as confirmed by the sharp signal around 810 cm −1 and by the appearance of the small shoulder around 710 cm −1 after annealing at 120 °C and 150 °C (curves (C) and (D) in the left panel) [56]. It is worth mentioning that the intensity of the shoulder at 710 cm −1 is still very small and that the Raman spectra all share a common feature around 950 cm −1 , which is characteristic of amorphous WO3 films [57]. All these observations, together with the XRD suggest that the slot-die-deposited WO3 films are characterized by a prevalent amorphous general character.…”
Section: Pure Wo 3 Films: Structural and Morphological Characterizationmentioning
confidence: 87%
“…Previous studies have reported the intrinsic reaction mechanism of WO 3 /elaectrolyte interfaces in various electrolytes [20][21][22][23]. The deposition of WO 3 thin films has been achieved through various techniques, including physical vapor deposition (PVD), chemical vapor deposition (CVD) [24], evaporation [25][26][27], electrodeposition [28], sputtering [29][30][31][32], sol-gel deposition [27,33], and spray pyrolysis technique [34][35][36][37]. The latter technique presents many advantages such as (i) short time deposition, (ii) simple technology, (iii) low-cost, (iv) no need for vacuum, and (v) large-scale area of thin film production.…”
Section: Introductionmentioning
confidence: 99%